Fifty key contemporary thinkers from structuralism to post-humanism - Lechte, John. (London Routledge, 2008)
This revised second edition from our bestselling Key Guides includes brand new entries on some of the most influential thinkers of the twentieth- and twenty-first century: Zizek, Bergson, Husserl, Heidegger, Butler and Haraway.
Includes bibliographical references and index.
Keywords: Philosophy, Modern --20th century